2008
DOI: 10.2174/157340608786242089
|View full text |Cite
|
Sign up to set email alerts
|

Hemoglobin Enhances the Biological Activity of Synthetic and Natural Bacterial (Endotoxic) Virulence Factors: A General Principle

Abstract: Although hemoglobin (Hb) is mainly present in the cytoplasm of erythrocytes (red blood cells), lower concentrations of pure, cell-free Hb are released permanently into the circulation due to an inherent intravascular hemolytic disruption of erythrocytes. Previously it was shown that the interaction of Hb with bacterial endotoxins (lipopolysaccharides, LPS) results in a significant increase of the biological activity of LPS. There is clear evidence that the enhancement of the biological activity of LPS by Hb is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…This interpretation is strengthened by recent observations that haemoglobin and part structures are enhancing the biological activity of LPS, concomitant with a clear expression of a cubic SAXS pattern for LPS Rc as well as Ra. 24,25…”
Section: Discussionmentioning
confidence: 99%
“…This interpretation is strengthened by recent observations that haemoglobin and part structures are enhancing the biological activity of LPS, concomitant with a clear expression of a cubic SAXS pattern for LPS Rc as well as Ra. 24,25…”
Section: Discussionmentioning
confidence: 99%
“…A series of early studies revealed that hemoglobin synergistically increases the production of TNF and other cytokines by macrophages exposed to LPS and other activators(1-3). It has previously been proposed that hemoglobin enhances the presentation of LPS to immune cells, resulting in a synergistic increase in cytokine release (3-5). Other studies, however, implicated a critical role of the heme moiety of hemoglobin in the mechanism that enhances macrophage TNF release during endotoxemia (6).…”
Section: Introductionmentioning
confidence: 99%
“…However, HB, which promotes LPS toxicity [ 11 ], produced an increase in OD signals in the competitive ELISAs tested. Although there is still some controversy as to whether the active forms of LPS are monomers or multimers with a particular conformation [ 52 ], most of the available data attribute the enhanced LPS biological activity to the ability of certain proteins to disaggregate LPS (decrease in the size of aggregates) and/or to promote transition from multilamellar structures to cubic structures [ 16 , 25 , 53 ]. Our results are consistent with this type of interaction, as the enhanced OD values obtained in the competitive ELISAs are probably due to disaggregation of LPS.…”
Section: Discussionmentioning
confidence: 99%